Scenic Imagery in the Poetry of Baland al-Haidari - حسين , د. نوفة علي (Thi Qar Arts Journal, 2025)
Scenic imagery in poetry is considered one of the most inspiring and innovative elements that a poet can incorporate into their poem. Its purpose is to create an imaginary event in time and space, or to present a finely crafted visual description of an action, character, or specific state. This technique can be observed in Arabic poetry since ancient times, with numerous examples found in pre-Islamic poetry and throughout the various historical stages of Arabic verse.Modern Arab poets have benefited from the language of cinema, which has led some poetic experiences to resemble films by employing cinematic techniques, including scenic imagery. Interestingly, from this perspective, the Iraqi poet Baland al-Haidari began to explore—through his vast imagination and sensory awareness—the expressive possibilities offered by cinematic arts. These tools contributed to the creation of expressive images and scenes that gave his texts a distinctly cinematic tendency, especially evident in descriptive or scenic passages, pushing poetic expression beyond conventional boundaries.